Exploring the essential role of employability skills in TVET - Mohd Puad, Mohd Hazwan; Nan, Yue (Faculty of Educational Studies, Universiti Putra Malaysia (UPM), 2024)
In the 21st century, new technologies are rapidly transforming manufacturing processes, workplaces, and lifestyles; rapid technological advancements are reshaping industries and redefining workplace requirements, leading to a pronounced skills gap in the labor market. This paper focuses on the critical role of employability skills within Technical and Vocational Education and Training (TVET) systems in addressing this challenge. Employability skills—such as communication, problem-solving, and adaptability—are increasingly essential for bridging the skills gap, enhancing graduate employment, and fostering sustainable career development. By integrating these skills into TVET curricula, educational institutions can better align training programs with the evolving needs of the labor market. This paper synthesizes existing research on the impact of employability skills on employment, career success, and labor market demands. It highlights the importance of their systematic inclusion in TVET programs to prepare graduates for the modern workforce and promote inclusive economic progress.